Learning Innovation for Aisyiyah Elementary School Teachers in Mataram City: The Development of AI-Generated Teaching Media - Wiraatmaja, Triastama; Sabgini, Kharisma Naidi Warnanda; Prastiyowati, Santi (PROJECT (Professional Journal of English Education), 2025)
This community service program focuses on leveraging artificial intelligence (AI) to enhance teachers’ competence at the Aisyiyah elementary level in Mataram city. The study aims to introduce an innovative teaching and learning tool: AI-generated teaching media. These media are designed to incorporate visually appealing graphics and contextually relevant contents align with the curriculum. The development process integrates advanced AI technologies to create customized content, age-appropriate materials, culturally relevant, and pedagogically effective media. The project employs a participatory approach, involving teachers in the design and evaluation phases to ensure that the media address the learning needs and preferences of the target audience. This program employed a qualitative methodology, including observations, tutorials, and focus group discussions, to evaluate the effectiveness of the AI-generated media in improving teachers’ competence. Data were analyzed to determine how this innovative approach impacts teaching practices and learning outcomes. This initiative aligns with broader educational goals to incorporate technology as 21st century skills among young learners, and as ongoing attempts to make AI more engaging and accessible in Indonesia. This study is expected to be a replicable model, to demonstrate the potential of AI to revolutionize education, and to inform how innovative tools can transform traditional learning experiences.